An empirical study of nation branding for attracting internationally mobile skilled professionals. Issue 3 (8th June 2015) - Silvanto, Sari; Ryan, Jason; McNulty, Yvonne
Abstract : Purpose: – The purpose of this paper is to empirically assess the importance for nations of key institutional, economic, and societal factors for attracting skilled professionals from abroad. It examines the existing literature on international talent mobility and empirically tests the validity of nation branding as a strategy for attracting internationally mobile skilled professionals. Design/methodology/approach: – The authors use secondary data from the World Economic Forum, the United Nations Development Programme (UNDP) and the Martin Prosperity Institute to test six hypotheses concerning factors that attract internationally mobile skilled professionals to a foreign country to live and work. Findings: – The study finds that conditions of employment, quality of life, good governance, and tolerance towards people of diverse backgrounds are key issues that need to be holistically emphasized in successful nation branding campaigns aimed at attracting highly skilled professionals from abroad. Originality/value: – The authors use strong secondary data to reduce common method bias in the results which show that "macro" factors sway internationally mobile skilled professionals to favor some countries over others. The authors contribute to the literature on international talent flows by conceptualizing nation branding as a framework through which a variety of push and pull factors can be examined to entice and attract internationally mobile skilled professionals to a particular host-country. The findings will apply to several different types of skilled professionals including self-initiated expatriates, self-initiated corporate expatriates, and third country nationals and local foreign hires.